(untitled) (Amsterdam, 2011)
Global concern for energy security and environmental protection has put great emphasis on the search for alternative energy sources, particularly for the transport sector. Biofuels have emerged as a highly promising source of alternative energy, and have drawn global R&D for their production using biomass.
Keywords: Biomass energy,Năng lượng sinh khối